Maus, a survivor's tale. I, My father bleeds history - Spiegelman, Art. (New York : Pantheon Books, 1986)
The story, in comic book form, of the author's parents' experiences as Jews in Poland prior to and during WWII. Illustrations portray Jews as mice and Nazis as cats.
"Chapters 1 through 6 first appeared, in somewhat different form, in Raw magazine between 1980 and 1985"--T.p.verso.
"Prisoner on the Hell Planet" originally appeared in Short Order Comix #1, 1973"--T.p. verso.
Maps on p. [4] of cover.
Sequel: Maus II: A Survivor's Tale; And Here My Troubles began.
Keywords: Spiegelman, Art -- Comic books, strips, etc; Spiegelman, Vladek -- Comic books, strips, etc; Children of Holocaust survivors -- United States -- Biography -- Comic books, strips, etc; Holocaust survivors -- United States -- Biography -- Comic books, strips, etc; Holocaust, Jewish (1939-1945) -- Poland -- Biography -- Comic books, strips, etc